The spectral properties of two-electron quantum dot - El-Said, M (Elsevier Science Bv, 2002)
The spectra of two interacting electrons, confined in a quantum dot, is studied for any ratio of coulomb to confinement energy by using the shifted 1/N expansion method. An explanation is given to the energy-level crossings which occur in the quantum dot spectra. The oscillation of the spin of the ground state as the magnetic field varies is studied. Based on comparisons, the method shows very good agreement with very recent results produced by using WKB-approximation and exact numerical methods. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: Magnetic-Field; Dynamic-Response; Energy-Spectra; 2 Electrons; Spectroscopy; Helium